(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
English language is the first spoken language around the world, and it is the formal language for communication in my multilingual Saudi context. This paper is to conduct a further investigation to findings of a similar study conducted by Jumanto (2014) exploring the functions of phatic communication among English native speakers. Furthermore, this study aims at exploring phatic communication among native and nonnative English speakers in my workplace to have a healthy distinguished working atmosphere through guiding them to build a solid social relationship at workplace through involving in various communicative situations for the sake of rapport, not to convey information. For instance, to greet or reply to a greeting properly, start or end conversations with native or nonnative colleagues to avoid any inconvenience or misunderstanding due to the likely distinctions related to their different social or cultural backgrounds which may affect negatively on their relationship. To achieve this, an exploratory mixed study will be conducted in two phases using a questionnaire for quantitatively collected data, and then conducting semi-structured interviews for the same population to qualitatively collect data to have reliable findings. Additionally, the findings of this study reflect a great harmony among the phatic expressions used by native and nonnative speakers, especially native English speakers who try speaking the mother language, Arabic, of the nonnative English speakers for the purpose of greeting or starting interaction with each other. Accordingly, further research investigation could be conducted to explore the impact of phatic communication functions among native and nonnative speakers of any other languages on learning a second or a foreign language.